The BEAF-32 Protein Directly Interacts with Z4/putzig and Chriz/Chromator Proteins in Drosophila melanogaster. - Melnikova, L.S.; Molodina, V.V.; Kostyuchenko, M.V.; Georgiev, P.G.; Golovnin, A.K. (Doklady. Biochemistry and Biophysics, 2021)
In Drosophila, the BEAF-32, Z4/putzig, and Chriz/Chromator proteins colocalize in the interbands of polytene chromosomes. It was assumed that these proteins can form a complex that affects the structure of chromatin. However, the mechanism of the formation of such a complex has not been studied. We have proved for the first time that the BEAF-32, Z4/putzig, and Chriz/Chromator proteins interact directly with each other and localized the protein domains that provide multiple protein-protein interactions. Based on the data obtained, we developed a model of the mechanism of the formation the BEAF/Z4/Chriz complex and its recruitment to chromatin.